Hypervalent Iodine(III) Reagent Mediated Regioselective Cycloaddition of Aldoximes with Enaminones; European Journal of Organic Chemistry; Vol. 2019, iss. 39 - Yoshimura A. Akira; Jarvi M. E. Melissa; Shea M. T. Michael; Makitalo C. L. Cody; Rohde G. T. Gregory; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Saito A. Akio; Zhdankin V. V. Viktor Vladimirovich (2019, 2019)
Title screen